Postintubation membranous tracheal rupture - B Grayet; B Duysinx; B Ghaye (Journal of the Belgian Society of Radiology, 2010)
Background: A 41-year-old female underwent general anaesthesia for teeth surgery. No complication occurred during and immediately after surgery. Three days later, she presented to the Emergency Department with retrosternal pain and subcutaneous emphysema at the level of the upper chest and the neck.